Kako prevoditi suvremeni francuski žargon? Traduktološka analiza hrvatskog prijevoda romana Volim sutra Faize Guene - Mirna Sindičić Sabljo ([sic])
Just like tomorrow (Kiffe kiffe demain), a novel written by the French author Faize Guene, was published in 2004. Shortly after its publication, the novel was translated into twenty foreign languages. The Croatian translation appeared in 2006. Kiffe kiffe demain describes a year in the life of a teenage girl of Moroccan origin, living in one of the suburbs in northern Paris. The novel is written mostly in slang. The aim of this paper is to analyse the lexical, grammatical and syntactic specifics of the language in which the novel was written, to determine the difficulties that the translator encountered in translating them, and to analyze the Croatian translation of the novel Kiffe kiffe demain. The analysis is based on close reading and comparative analysis of the original text and its translation, taking into account the linguistic, stylistic, textual, and cultural issues relevant to the translation. Comparative analysis of the original and the translation, apart from their philological, lexical, formal-stylistic, and poetic features, also encompasses the cultural aspect with reference to contemporary translation theories.